Telemedicine in the treatment of addictions. Issue 4 (9th July 2022) - Caballeria, Elsa; López-Pelayo, Hugo; Matrai, Silvia; Gual, Antoni
Abstract : Purpose of review: The purpose of this update is to provide an overview of recent research publications (January 2020–January 2022) on real-time telemedicine solutions for the management of addictions (alcohol, tobacco, opioids, and other drugs). Recent findings: Motivational interviewing by real-time telemedicine showed effectiveness in youth and adults for risky alcohol use and alcohol use disorders, even when a concurrent mental health disorder exists. Live telemedicine is well accepted for managing tobacco use disorders. The range of interventions for treating opioid use disorder by real-time telemedicine is large and has been increased due to the coronavirus disease 2019 (COVID-19) pandemic (prescription of opioid agonists, peer-to-peer support, counseling, and group therapy). Summary: The COVID-19 pandemic has accelerated the implementation of real-time telemedicine and, in parallel, research has been conducted to test its effectiveness. Videoconferencing and telephone interventions are supported by solid evidence for risky alcohol use and alcohol use disorder, tobacco use disorder and opioid use disorder. The Integration of other types of telemedicine (asynchronous telemedicine and remote monitoring) and with the entire health system is lacking. Many areas and vulnerable populations (e.g., homeless, elderly, and cannabis use disorders) need more attention.